Proteomic Analysis of Hop Bitter Compound Iso-α-acid Tolerance in Beer Spoilage Lactobacillus casei 2-9-5. (2nd October 2021) - Zheng, Feiyun; Wang, Tianmu; Niu, Chengtuo; Jia, Yun; Zheng, Ruilong; Liu, Chunfeng; Wang, Jinjing; Li, Qi
Abstract: Lactobacillus species are the main spoilage bacteria in beer production and storage. The prerequisite for Lactobacillus species to grow in beer is to be able to resist the hop bitter compound iso-α-acid. This study examined the underlying iso-α-acid resistance mechanism of L. casei strain 2-9-5 through proteomic analysis. The significantly up-regulated proteins in L. casei 2-9-5 under 0.04% iso-α-acid are mainly involved in carbohydrate metabolism, energy generation, organic acids metabolism, and cell wall composition. Based on the proteomic analysis, it is proposed that organic acids may be important for L. casei 2-9-5 to resist iso-α-acid. The extracellular organic acids concentrations in L. casei 2-9-5 under iso-α-acid pressure were significantly higher than the control. Furthermore, additions of oxalic acid, tartaric acid, pyruvate, and ketoglutaric acid in the media were able to enhance the growth of L. casei 2-9-5 under iso-α-acid pressure. These phenomena were also observed in different Lactobacillus species, with different iso-α-acid resistance ability since the addition of organic acids also promoted the growth of these strains. Together, the data supports that organic acids are closely related to the resistance ability of Lactobacillus species towards iso-α-acid.